СТАНОВЛЕННЯ ТА РОЗВИТОК ПЕДАГОГІКИ КРАСИ ЯК ТЕОРЕТИЧНОЇ ОСНОВИ ЕСТЕТИЧНОЇ ОСВІТИ І ВИХОВАННЯ МОЛОДІ (Педагогіка вищої та середньої школи, 2007)
It is viewed in the article the pedagogy of Beauty as a field of scientifically-pedagogical knowledge, connected with aesthetical education of youth, forming aesthetical culture of a personality, enriching of his/her spiritually-creative ties with art.